Observations of a Commercial Weight Loss Program on Physical Function and Selected CVD Risk Factors. Issue 12 (2020) - Rogers, Renee J.; Kovacs, Sara J.; Collins, Katherine A.; Raybuck, Shawn; Collins, Audrey M.; Marcin, Marissa L.; Foster, Gary D.; Jakicic, John M.
Abstract : ABSTRACT: Commercial programs are effective for reducing body weight and cardiometabolic risk factors. However, there are limited data on the additional health benefits that may result from weight loss achieved through a commercial program. This study reports on observations from a commercial weight loss program on physical function and selective cardiovascular disease risk factors in adults with obesity. Three hundred adults with obesity (age, 47.3 ± 12.6 yr; body mass index, 33.2 ± 4.4 kg·m −2 ) participated in a 6-month commercial weight loss program (WW, formerly Weight Watchers). Measures included weight, height, body mass index, waist circumference, physical function using the 6-min walk test and the sit and reach test, resting blood pressure, and resting heart rate. There was significant weight loss of 4.2 ± 3.7 kg (4.7% ± 4.1%) and 4.9 ± 5.7 kg (5.5% ± 6.2%) at 3 and 6 months, respectively ( P < 0.001). Sit and reach, walking distance during the 6-min walk, and gait speed significantly improved across the 6-month intervention ( P < 0.001). In addition, there were significant decreases in resting blood pressure and heart rate. A commercial weight loss program results in improvements in measures of physical function and selective cardiovascular disease risk factors. These findings support the potential of commercial programs to affect health-related measures in adults with obesity.